Efficacy of dihydroartemisinin/piperaquine in patients with non-complicated Plasmodium falciparum malaria in Yaoundé, Cameroon. (28th August 2021) - Mairet-Khedim, Mélissa; Nsango, Sandrine; Ngou, Christelle; Menard, Sandie; Roesch, Camille; Khim, Nimol; Srun, Sreynet; Iriart, Xavier; Lanot, Thomas; Otam, Laure; Abega, Francis; Ayong, Lawrence; et al.
Abstract: Background: Dihydroartemisinin/piperaquine is increasingly used for the treatment of uncomplicated Plasmodium falciparum malaria in Africa. The efficacy of this combination in Cameroon is poorly documented, while resistance to dihydroartemisinin/piperaquine readily spreads in Southeast Asia. Objectives: This study evaluated the clinical efficacy of dihydroartemisinin/piperaquine in Cameroon, as well as the molecular profile and phenotypic susceptibility of collected isolates to dihydroartemisinin and piperaquine. Patients and methods: Dihydroartemisinin/piperaquine efficacy in 42 days was followed-up for 138 patients presenting non-complicated falciparum malaria. Piperaquine concentration was determined at day 7 for 124 patients. kelch13 gene polymorphisms ( n  =   150) and plasmepsin2 gene amplification ( n  =   148) were determined as molecular markers of resistance to dihydroartemisinin and piperaquine, respectively. Parasite susceptibility to dihydroartemisinin and piperaquine was determined using validated in vitro survival assays. Results: The efficacy of dihydroartemisinin/piperaquine treatment was 100% after PCR correction. The reinfections were not associated with a variation of piperaquine concentration at day 7. Ninety-six percent (144/150) of the samples presented a WT allele of the kelch13 gene. Two percent (3/150) presented the non-synonymous mutation A578S, which is not associated with resistance to dihydroartemisinin. No duplication of the plasmepsin2 gene was observed (0/148). All the samples tested in vitro by survival assays ( n  =   87) were susceptible to dihydroartemisinin and piperaquine. Conclusions: Dihydroartemisinin/piperaquine has demonstrated excellent therapeutic efficacy with no evidence of emerging artemisinin or piperaquine resistance in Yaoundé, Cameroon. This observation suggests that dihydroartemisinin/piperaquine could be a sustainable therapeutic solution for P. falciparum malaria if implemented in areas previously free of artemisinin- and piperaquine-resistant parasites, unlike Southeast Asia.